Emotion and Stress Related Eating and Personality Dimensions Predict Food Addiction: Implications for Personalized Weight Management and Primary Prevention - Eva Klanduchova; Lucia Adamovska (Mediterranean Journal of Clinical Psychology)
Background: Food addiction constitutes a novel health concern with potential consequences for both psychological and physical well-being. While the etiology of Food addiction is likely multifactorial, additional factors beyond obesogenic environments need to be explored. Therefore, we sought to examine the relationships between five-factor personality domains, Food addiction and coping styles related to eating (Emotion and stress related eating) starting from the hypothesis that Food addiction may be determined by coping styles related to eating (based on a Transactional Model of Stress and Coping) as well as specific personality traits